Ethical dilemmas and legal ambiguity in China: a chain mediation model linking suicide rumination, legitimization, and acceptance among acutely-ill adults - Liu, Guo; Liu, Kai (Frontiers in Psychology, 2024)
Background This study explores the complex intersection of euthanasia, legal ambiguities, cultural attitudes, and the psychology of suicide among seriously ill patients in China. It addresses the lack of clear legislation on euthanasia and doctor-assisted killing, the impact of cultural and philosophical beliefs, and the evolution of legal and ethical perspectives on suicide. Additionally, it examines the psychological aspects of suicide ideation in acutely-ill patients, focusing on factors like familial burden and loss of dignity. Method A survey was conducted with 356 Chinese adults, aged 23 to 64 years, using popular social media platforms in China. The study aimed to reflect a broad spectrum of the adult population in terms of age, education, and professional sectors. The research model involves suicide rumination as an independent variable, acutely-ill patients' suicide acceptance as a dependent variable, and three mediators: cognitive depression, ethical suicide acceptance, and suicide legitimization. Results The findings reveal a significant total effect of Suicide Rumination on Acutely-ill Patients' Suicide Acceptance, underlining a robust direct relationship that supports Hypothesis 1. The analysis indicates that Suicide Rumination is a significant predictor of Cognitive depression, explaining approximately 8.05% of its variance, thereby fully supporting Hypothesis 2a. However, the effect of Suicide Rumination on Ethical Suicide Acceptance did not emerge as significant, failing to support Hypothesis 2b, while its impact on Suicide Legitimization was also non-significant, not supporting Hypothesis 2c. Cognitive depression was found to have a substantial effect in the models for both Ethical Suicide Acceptance and Suicide Legitimization, supporting Hypotheses 3a and 3b. In the comprehensive model assessing Acutely-ill Patients' Suicide Acceptance, incorporating all mediators, a significant variance (R-squared = 0.6625) was explained. Notably, Suicide Rumination, Ethical Suicide Acceptance, and Suicide Legitimization all emerged as significant predictors of this acceptance, with varying effects, thus supporting Hypotheses 4a and 4b. The role of Cognitive depression in this model was marginally significant, offering limited support for Hypothesis 4c. Crucially, the indirect effects of Suicide Rumination on Acutely-ill Patients' Suicide Acceptance through different mediational paths varied in significance and impact. The indirect effect via Cognitive depression alone, and through the sequential combination of Cognitive depression and Ethical Suicide Acceptance, were significant, highlighting the nuanced role of these mediators. These findings underscore the importance of considering multiple pathways in understanding the dynamics of Suicide Rumination and its influence on the acceptance of suicide among acutely-ill patients. Conclusion This paper presents a comprehensive analysis of the legal, cultural, ethical, and psychological dimensions of euthanasia, doctor-assisted killing, and suicide in China. The findings highlight the significant direct and mediated effects of suicide rumination on the acceptance of suicide among acutely-ill patients. The study contributes valuable insights into the evolving bioethics and the interplay of various factors in the context of end-of-life decision-making in modern Chinese society.